1991
DOI: 10.1111/j.1365-2222.1991.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind cross‐over trial of oral sodium cromoglycate in patients with irritable bowel syndrome due to food intolerance

Abstract: Twenty patients with irritable bowel syndrome due to food intolerance were randomized to either oral sodium cromoglycate or placebo in a double-blind cross-over trial. The study consisted of treatment with either sodium cromoglycate or placebo for 8 weeks, followed by the cross-over treatment for 8 further weeks. Patients were allowed to eat the offending foods during the study. Eighteen patients completed the study. Analysis of patients' diary card scores showed a statistically significant difference in favou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
60
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 22 publications
0
60
0
Order By: Relevance
“…Thus, our data pave the way for considering the release of these mediators as a potential mechanism contributing to IBS pathophysiology. However, our study has some limitations, and a number of issues remain to be addressed, including the assessment of: (1) mediators (other than histamine and tryptase) of mast cell and nonmast cell origin, which are likely involved in the activation of sensory neurons; (2) participation of mechanical stimuli on the sensitization of sensory fibers; (3) causes underlying the increased release of mucosal mediators involved in sensory neuron activation [eg, psychologic factors, neurohormonal factors (eg, neuropeptides, corticotrophin releasing factor) food allergens, intestinal microflora, intestinal permeability]; (4) potential clinical correlates between sensory neural pathways activation evoked by mucosal mediators and abdominal pain perceived by patients; (5) clinical usefulness of inhibition of mast cell activation (eg, mast cell stabilizers, 36,37 anti-IgE antibodies, 38 inhibitors of the intracellular protein tyrosine kinase, Syk 39 ), or antagonism of the effects of mast cell mediators (eg, histamine and proteases receptor antagonists). These still open issues could represent the objective of future ad hoc-designed studies.…”
Section: Mast Cell Mediators From Ibs Patients Excite Nociceptive Neumentioning
confidence: 99%
“…Thus, our data pave the way for considering the release of these mediators as a potential mechanism contributing to IBS pathophysiology. However, our study has some limitations, and a number of issues remain to be addressed, including the assessment of: (1) mediators (other than histamine and tryptase) of mast cell and nonmast cell origin, which are likely involved in the activation of sensory neurons; (2) participation of mechanical stimuli on the sensitization of sensory fibers; (3) causes underlying the increased release of mucosal mediators involved in sensory neuron activation [eg, psychologic factors, neurohormonal factors (eg, neuropeptides, corticotrophin releasing factor) food allergens, intestinal microflora, intestinal permeability]; (4) potential clinical correlates between sensory neural pathways activation evoked by mucosal mediators and abdominal pain perceived by patients; (5) clinical usefulness of inhibition of mast cell activation (eg, mast cell stabilizers, 36,37 anti-IgE antibodies, 38 inhibitors of the intracellular protein tyrosine kinase, Syk 39 ), or antagonism of the effects of mast cell mediators (eg, histamine and proteases receptor antagonists). These still open issues could represent the objective of future ad hoc-designed studies.…”
Section: Mast Cell Mediators From Ibs Patients Excite Nociceptive Neumentioning
confidence: 99%
“…Previous studies of mast cell stabilisers and anti-inflammatory agents in irritable bowel syndrome Although there were some poorly designed trials two decades ago, claiming to show that sodium cromoglycate was effective for IBS, [16][17][18] these studies remain unconfirmed and the treatment is not widely used. There have been other smaller studies targeting mast cells with antihistamines, such as ketotifen; 19 although this reduced visceral hypersensitivity, it had no effect on mast cell numbers or release of mast cell mediators.…”
Section: Existing Researchmentioning
confidence: 99%
“…More recently, a subset of IBS-d patients with increased intestinal MC identified in biopsy specimens have been reported to respond well to MC stabilizers termed ''mastocytic enterocolitis'' [13]. A handful of clinical trials have also reported symptomatic improvement in IBS treated with MC stabilizers [14][15][16][17][18][19][20]. The association between MC and diarrhea/abdominal cramps, is further highlighted by the fact that these symptoms are prevalent in patients with intestinal involvement by systemic mastocytosis [21,22].…”
mentioning
confidence: 99%
“…Short-term administration of the ''MC stabilizer'' sodium cromoglycate in combination with or without an elimination diet has yielded inconsistent results, with some authors reporting symptomatic improvement and others failing to observe any [14][15][16][17][18][19]. Only two of these studies were randomized and double-blinded [16,17], with one evaluating only IBS-d patients (n = 20) [16] and the second including patients with chronic unexplained diarrhea (n = 40) [17]. An 8-week treatment with sodium cromoglycate significantly improved symptoms in the first study [16], but only about 30 % of patients reported a significant decrease of stool frequency after a 4-week regimen in the second study, with no improvement in the placebo group [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation